Popularization of culture as a component of nation branding: A theoretical perspective on Ukraine’s cultural identity - Ivashchuk, Antonina; Polozhentseva, Kateryna; Pasenko, Inha; Krypchuk, Mykola; Lachko, Olga (My University, 2025)
This article examines the popularization of culture as a key component of nation branding, focusing on Ukraine in the context of ongoing war and geopolitical contestation. Drawing on theories of nation branding, soft power, imagined communities, and strategic narratives, the study explores how cultural identity is mobilized to support both external image-making and internal nation-building. Particular attention is paid to the tension between reinforcing traditional cultural narratives and promoting cultural transformation oriented toward modernity and European integration. Empirically, the article analyses survey data collected in 2024 from 248 Ukrainian respondents aged 21–35, divided into two groups according to their attitudes toward cultural continuity versus reform in nation branding. Using the “My Nation – Foreign Nation” semantic differential and the Schwartz Value Survey, the study identifies significant differences in ethnic self-perception and cultural value orientations. While one group emphasizes autonomy, creativity, and innovation, the other prioritizes hierarchy, belonging, and national unity. The findings suggest that Ukraine’s nation branding cannot rely on a single cultural narrative but must integrate historical authenticity with cultural innovation. The article argues that effective nation branding in wartime Ukraine functions simultaneously as cultural diplomacy, psychological resilience-building, and a strategic response to external disinformation.
Keywords: брендинг нації; національна ідентичність українська; українська культура; cultural resilience; культурна дипломатія; digital diplomacy; national values